Analisis Kausalitas antara Konsumsi Energi Fosil, Pendapatan per Kapita, dan Foreign Direct Investment di Negara-Negara ASEAN - Maisa Mahran Rahmahhani; Siti Fatimah Zahra; Sri Indah Nikensari (INDO PUBLISHING, 2026)
This study aims to analyze the causal relationship between Fossil Energy Consumption, Per Capita Income, and Foreign Direct Investment (FDI) in six ASEAN countries over the period 2005–2024. This research employs a quantitative approach using balanced panel data comprising 120 observations. The analytical framework includes panel stationarity tests, Pedroni panel cointegration tests, and the Dumitrescu-Hurlin panel causality test augmented with the Toda-Yamamoto procedure (DH-TY). This framework is selected due to its suitability for data characterized by mixed integration orders of I(0) and I(1) and heterogeneous panel structures. Data processing is conducted using EViews 12. The results reveal three significant unidirectional causal relationships, namely from Per Capita Income to FDI (prob. 0.0000), from Fossil Energy Consumption to FDI (prob. 0.0002), and from Per Capita Income to Fossil Energy Consumption (prob. 0.0292), while no reverse causality is found in the opposite directions.